The life and death of Leon Trotsky [L. Tročkij]. Transl. from the French by A.J. Pomerans. Introd. by V. Kibaltchich [V.V. Kibal'čič] (Wildwood House, 1975)
With index. Original title: Vie et mort de Leon Trotsky, 1951. Victor Serge is ps. of Viktor L'vovič Kibal'čič.